Safety and efficacy of herbal medicine for acute intracerebral hemorrhage (CRRICH): a multicentre randomised controlled trial. Issue 5 (9th May 2019) - Zeng, Liling; Tang, Guanghai; Wang, Jing; Zhong, Jianbin; Xia, Zhangyong; Li, Jiexia; Chen, Guangsheng; Zhang, Yongbo; Luo, Saihua; Huang, Gan; Zhao, Qianshan; Wan, Yue; et al.
Abstract : Objective: To evaluate the safety and efficacy of removing blood stasis (RBS) herbal medicine for the treatment of acute intracerebral haemorrhage (AICH) within a 6-hour time window. Study design: A randomised, multicentre, double-blind, placebo-controlled study performed in 14 hospitals in China. Participants and interventions: Patients with AICH were randomly assigned to receive a placebo, the ICH-1 (Intracerebral Haemorrhage) formula (eight herbs, including the RBS herbs hirudo and tabanus ) or the ICH-2 formula (six herbs without the RBS herbs hirudo and tabanus ) within 6 hours of ICH onset. Outcomes: The primary safety outcome was the incidence of haematoma enlargement at 24 hours and at 10 days after treatment. The secondary outcome was the incidence of poor prognosis (mortality or modified Rankin Scale score ≥5) assessed at 90 days after symptom onset. Results: A total of 324 subjects were randomised between October 2013 and May 2016: 105 patients received placebo; 108 patients received the ICH-1 formula; and 111 patients received the ICH-2 formula. The incidence of haematoma enlargement at 24 hours was 7.8% in the placebo group, 12.3% in the ICH-1 group and 7.5% in the ICH-2 group; the incidence of haematoma enlargement on day 10 was 1.1% in the placebo group, 1.1% in the ICH-1 group, and 3.1% in the ICH-2 group, with no significant differences among the groups (P>0.05). The mortality rates were 3.8% in the placebo group, 2.8% in the ICH-1 group, and 0.9% in the ICH-2 group; the incidences of poor prognosis were 7.1% in the placebo group, 6.0% in the ICH-1 group and 4.8% in the ICH-2 group at 3 months, with no significant differences among the groups (p>0.05). However, the overall frequency of treatment-emergent adverse events in the ICH-1 group (12.1%) was higher among the three groups (5.8% and 2.8%, respectively, p < 0.05). All three cases of serious adverse events were in the ICH-1 group. Conclusions: Ultra-early administration of ICH-1 formula for AICH patients did not exert significant beneficial effects on clinical outcomes but increased the risk of bleeding, which probably resulted from the inclusion of RBS herbal medicines in ICH-1. Trialregistration number: NCT01918722 .